PREVAIL IV: A Randomized, Double-Blind, 2-Phase, Phase 2 Trial of Remdesivir vs Placebo for Reduction of Ebola Virus RNA in the Semen of Male Survivors. (12th March 2021) - Higgs, Elizabeth S; Gayedyu-Dennis, Dehkontee; Fischer II, William A; Nason, Martha; Reilly, Cavan; Beavogui, Abdoul Habib; Aboulhab, Jamila; Nordwall, Jacqueline; Lobbo, Princess; Wachekwa, Ian; Cao, Huyen; Cihlar, Tomas; et al.
Abstract: Background: Ebola virus RNA persists in the semen of male Ebola survivors for months to years after the acute infection, and male-to-female sexual transmission of the virus is well documented. We investigated whether remdesivir can safely reduce persistence of seminal Ebola virus RNA. Methods: We recruited men with persistent seminal Ebola RNA in Liberia and Guinea. Participants were randomized 1:1 to receive intravenous remdesivir (GS-5734; Gilead Sciences) or matching placebo administered once daily by intravenous infusion over 1 hour on 5 consecutive days. Stratification was by country and number of positive (1 or 2) preenrollment semen tests. We evaluated the difference in mean assay negativity rate (ANR), that is, the proportion of negative tests for each participant in each group in the treatment (days 1–28) and follow-up (months 2–6) phases on an intention-to-treat basis. Results: We enrolled 38 men from July 2016 through June 2018. The mean treatment phase ANRs were 85% (standard deviation [SD] = 24%) and 76% (SD = 30%) in the remdesivir and placebo arms, respectively ( P = .270). The mean follow-up phase ANRs were 96% (SD = 10%) and 81% (SD = 29%) in the remdesivir and placebo arms, respectively ( P = .041). The 5-day remdesivir regimen was well tolerated with no safety concerns. Conclusions: In this small trial, remdesivir 100 mg/day for 5 days safely reduced the presence of Ebola virus RNA in the semen of Ebola survivors 2 to 6 months after administration. A larger follow-up study is necessary to confirm results. Clinical Trials Registration . NCT02818582 Abstract : Intravenous remdesivir safely reduces Ebola virus RNA in the semen of Ebola survivors 2 to 6 months after treatment. Remdesivir's effect on post-Ebola syndrome must await a larger confirmatory study with participants closer to their acute disease.